Debt peonage (enganche) and free labor. Debts and incomes on the Perú-París coffee plantation, Chiapas, México (1919-1941) - Fenner, Justus (2022)
Mexican post-revolutionary historiography on labor relations in the state of Chiapas has painted a one-sided picture by limiting its interpretations to a simplistic view between exploiter and exploited. This reductionist attitude has denied regional diversity in terms of geography and population as well as it ignored deliberately the changes and advances –driven by the needs of the international market– that have taken place since the end of the 19th century, specifically in labor relations between coffee plantation and the indigenous population. The analysis of the internal documentation of the Perú-París plantation aims to open up the historiographic panorama with a differentiated vision of the labor reality in the first half of the 20th century in Chiapas.